Lacustricola margaritatus, a new species of lampeye from the Lake Victoria and Lake Kyoga basins in eastern Africa (Cyprinodontiformes: Procatopodidae) - Nagy, Béla; Watters, Brian R. (Zootaxa, 2022)
Lacustricola margaritatus, a new species inhabiting small streams and swamps in the Lake Victoria basin in north-western Tanzania and southern Uganda, and the Lake Kyoga basin in central Uganda, is described. Lacustricola margaritatus is a small species with a moderately deep body, moderate dimorphism and pronounced dichromatism. It is distinguished from all other Procatopodidae by the following unique combination of characters: live male body colour pattern with vertically-elongated iridescent light blue patches at scale centres, forming a striped appearance of dotted longitudinal lines on the flanks, particularly evident in the two or three series below the mid-longitudinal line; male having deeply coloured unpaired fins with orange-brown in the proximal and median parts and a narrow black distal band; male with a yellow base along the pectoral fin; female with dark grey scale margins and dark grey patches on scales along mid-longitudinal series creating a narrow dark grey stripe; both sexes showing inconspicuous postopercular blotch; and in both sexes, the cephalic sensory system is entirely situated in open grooves at all levels. The new species has previously often been misidentified as L. pumilus, originally described as inhabiting the Lake Tanganyika basin in north-eastern Zambia, or 'L.' centralis, from the Lake Rukwa basin in south-western Tanzania. Lacustricola margaritatus differs from the above two species by morphometric and meristic characters, body and fin colouration, and in arrangement of the cephalic sensory system.